2019
DOI: 10.7554/elife.45833
|View full text |Cite
|
Sign up to set email alerts
|

Combining genomics and epidemiology to analyse bi-directional transmission of Mycobacterium bovis in a multi-host system

Abstract: Quantifying pathogen transmission in multi-host systems is difficult, as exemplified in bovine tuberculosis (bTB) systems, but is crucial for control. The agent of bTB, Mycobacterium bovis, persists in cattle populations worldwide, often where potential wildlife reservoirs exist. However, the relative contribution of different host species to bTB persistence is generally unknown. In Britain, the role of badgers in infection persistence in cattle is highly contentious, despite decades of research and control ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(148 citation statements)
references
References 85 publications
(126 reference statements)
11
128
2
Order By: Relevance
“…However, as in the previous reports, this study could not determine the direction(s) of transmission between the two species. Recent work 17 suggests that analysis of whole genome sequence data from badger and cattle isolates in the same geographical locations might allow a better quantification of the roles of badgers and cattle in any inter-species transmission. The authors' findings suggested that in Woodchester Park, England, within species transmission occurred at higher rates than between species transmission and that transmission occurred more frequently from badgers to cattle than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…However, as in the previous reports, this study could not determine the direction(s) of transmission between the two species. Recent work 17 suggests that analysis of whole genome sequence data from badger and cattle isolates in the same geographical locations might allow a better quantification of the roles of badgers and cattle in any inter-species transmission. The authors' findings suggested that in Woodchester Park, England, within species transmission occurred at higher rates than between species transmission and that transmission occurred more frequently from badgers to cattle than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem investigations have revealed progressive disease in some infected badgers with the potential to shed bacteria [23], and longitudinal sampling of live animals suggests the existence of a sub-group that persistently shed from multiple sources [24]. Both epidemiological field studies [24] and molecular typing [4] provide evidence for the persistence and transmission of infection amongst badgers, which is consistent with their role as a maintenance host. Although increases in their abundance may have contributed to the emergence of wild hosts as significant players in the epidemiology of TB, the risk of transmission to cattle posed by each host species is also related to the number of viable mycobacteria excreted [21,24] and to behavioral, ecological, and farm management factors [6,7,25], which determine rates of direct and indirect contact with wildlife [2].…”
Section: Discussionmentioning
confidence: 68%
“…Evidence for TB maintenance in multi-host systems in Europe arises from molecular epidemiological studies demonstrating inter-species transmission between cattle, non-bovine domestic species, and wildlife [4,5]; observational studies reporting TB in domestic and wild animals as a risk factor for cattle [6,7]; and case reports of inter-species transmission [8]. Experimental studies have demonstrated the inter-species transmission of M. bovis under controlled and natural conditions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the Consistency Index for all positions on the E. coli reference chromosome. A low Consistency Index value for a position indicates a high degree of inconsistency with the chromosomal phylogeny and can be calculated by HomoplasyFinder as described in earlier studies [10,39,40]. As can be observed in Figure 3 isolates categorized as a low-level AmpC producer (no pampC gene and no known ampC promoter mutation) tested CTX resistant and contained an insertion in the spacer region (-16_-15insT), which has not been described by Tracz et al [6].…”
Section: Genomic Homoplastic Mutationsmentioning
confidence: 87%